Corporate Inversions: Going beyond Tax Incentives. Issue 1 (10th October 2019) - Col, Burcin; Liao, Rose; Zeume, Stefan
Abstract: We study tax and nontax incentives for corporate inversions in a hand-collected data set of 691 inversions out of 11 home countries into 45 host destinations over the 1996–2013 period. Even though lower tax rates generally attract inversions, only 2 of 5 firms invert into tax havens, and two-thirds of firms invert into host destinations with lower statutory tax rates than those faced at home. Moreover, firms invert to geographically close destinations with similar governance standards. Using staggered country-pair-level policy changes as experiments, we find that host-country governance may explain why not all firms invert. Received December 6, 2018; Editorial decision August 12, 2019 by Editor Andrew Ellul.